Aeolians, Aeolian migration: ancient tradition and historical realities - Solomatina, Elena Ivanovna (Античный мир и археология, 2023)
The article presents results of the study of the ancient tradition about the Aeolians in general and about the Aeolian migration as a part of this tradition. The ancient literary tradition in the process of its formation, starting from the first scattered references to the Aeolians and ending with data on the territory of settlement, common language, self-name and reasons for finding a new place of residence, included not only historical facts, but, mainly, the ideas of the Greeks about these facts and their interpretation. And although these ideas contain anachronisms and are not always confirmed by other types of sources, nevertheless, these notions are of high interest for study, as they characterize the society that gave rise to them, reflecting its needs for creating iconic myths and forming an identity at a certain stage of its formation.